WORKSHOP PEMBELAJARAN TEKNOLOGI MULTIMEDIA UNTUK GURU SDN 4 CEPOKO KECAMATAN NGRAYUN GUNA PENGEMBANGAN BAHAN AJAR - Arin Yuli Astuti; Sugianti Sugianti (Universitas Muhammadiyah Ponorogo, 2019)
Multimedia can be used as a medium of entertainment and even education / learning. Currently children prefer to use gadgets as a learning medium, looking for information and even playing. So parents have to keep an eye on how far they are using gadgets to learn. Children are more interested in using electronic media to learn than to directly lecture or listen. To anticipate so that children are not bored and more interested, the teachers must be innovative in teaching and making teaching materials. SDN 4 Cepoko is one of the elementary schools located in Ngrayun District, Ponorogo Regency. Many teachers are still unfamiliar with Multimedia technology. Therefore the researcher tried to hold a workshop on multimedia technology as a teaching material for teachers at Cepoko 4 Elementary School.